2015
DOI: 10.1002/bip.22646
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray structure analysis reveals β‐turn mimicry by N‐amino‐imidazolidin‐2‐ones

Abstract: The conformation of the N-amino-imidazolidin-2-one (Aid) peptidomimetic was investigated using NMR spectroscopy and X-ray crystallography. In solution, the tetrapeptide model p-bromobenzoyl-Aid-l-Phe-N'-iso-propylamide (1) exhibited shielded and solvent exposed amide protons indicative of a turn conformation. In the crystal lattice of 1, four turn conformers were present in the unit cell differing primarily by the ring puckering of the Aid residue. Two pairs of β-turn conformers were observed each possessing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
(52 reference statements)
0
4
0
Order By: Relevance
“…X-ray crystallography of Aid peptide 76 indicated two pairs of 10-membered hydrogen-bonded conformers in the unit cell, each pair having respectively dihedral angles approaching ideal type II′ and type II β-turns (Figure ). In solution, NMR titration studies on 76 supported a 10-membered hydrogen bond between the benzamide carbonyl and the solvent-shielded isopropylamide NH. Like its Nai counterpart, the saturated Aid residue was situated at the i + 1 position in the β-turn but adopted both type II′ and type II geometries because of greater ring pucker flexibility.…”
Section: “Libraries From Libraries”mentioning
confidence: 99%
“…X-ray crystallography of Aid peptide 76 indicated two pairs of 10-membered hydrogen-bonded conformers in the unit cell, each pair having respectively dihedral angles approaching ideal type II′ and type II β-turns (Figure ). In solution, NMR titration studies on 76 supported a 10-membered hydrogen bond between the benzamide carbonyl and the solvent-shielded isopropylamide NH. Like its Nai counterpart, the saturated Aid residue was situated at the i + 1 position in the β-turn but adopted both type II′ and type II geometries because of greater ring pucker flexibility.…”
Section: “Libraries From Libraries”mentioning
confidence: 99%
“…It was found that a 16-fold dilution of the solution from 10 to 0.6 mM caused only a small shift in the N–H proton signals, suggesting that no intermolecular H-bonding-driven aggregation was present in the range of the concentrations tested. This was based on the fact that, when the concentration in DMSO- d 6 relative to that in CDCl 3 is increased, the donor proton causes a downfield shift due to the H-bonding with DMSO- d 6 . Since this effect is weakened by the presence of internal H-bonding, it can be used as an index with which to analyze the presence of H-bonding.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Furthermore, the aza-variants of the α-amino γ-lactam, so called N -amino-imidazolidin-2-one (Aid) residues were introduced into GHPR-6 analogues (e.g., 91d , Figure 9 ) by a sequence featuring alkylation of semicarbazone 39 with 1,2-dibromoethane, liberation of semicarbazide 90 with hydroxylamine in pyridine, peptide elongation and resin cleavage ( Scheme 9 ) [ 57 ]. In model peptides, Aid residues have been shown by NMR spectroscopy and X-ray crystallography to adopt the i + 1 position of well-defined, compact β-turns possessing intramolecular ten-member hydrogen bonds within types II and II’ geometry contingent on ring puckering [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, replacement of Ala 3 by these covalent constraining residues gave Furthermore, the aza-variants of the -amino -lactam, so called N-amino-imidazolidin-2-one (Aid) residues were introduced into GHPR-6 analogues (e.g., 91d, Figure 9) by a sequence featuring alkylation of semicarbazone 39 with 1,2-dibromoethane, liberation of semicarbazide 90 with hydroxylamine in pyridine, peptide elongation and resin cleavage (Scheme 9) [57]. In model peptides, Aid residues have been shown by NMR spectroscopy and X-ray crystallography to adopt the i + 1 position of well-defined, compact -turns possessing intramolecular ten-member hydrogen bonds within types II and II' geometry contingent on ring puckering [58]. In summary, the application of covalent constraint employing azaPro, azaPip, Agl, Bgl and Aid residues added support to conclude that an active turn conformer existed within the central residues of the hexapeptide.…”
mentioning
confidence: 99%